A critical study on legislating compulsory voting law in Malaysia / Nurul Nadia Syafini Zubir … [et al.] - Zubir, Nurul Nadia Syafini; Nor Asmadi, Nor Ayunni; Ku Nabil, Ku Latifah Zahidah; Syed Fisol, Sh Syaza Farhanah (Faculty of Law, 2014)
This paper is basically a study that determines the need to legislate compulsory voting law in Malaysia. As stated in Chapter One, this study is conducted due to legal criticism levelled against the present system of voting in Malaysia. Therefore, the need to legislate compulsory voting law in Malaysia is measured by analyzing whether or not the present system of voting in Malaysia is in fact muddled with problems. The conceptual and theoretical framework regarding compulsory voting have been laid down in Chapter Two of this paper and it is submitted that compulsory voting serves numerous advantages and based on the statistics and the evidences given by different scholars, the needs for compulsory are vital as the present system of voting in Malaysia is not effective enough to ensure higher turnout and to uphold democracy. Chapter Three examines the current legal positions in three countries that enforced compulsory voting in their system which are Australia, Singapore and Belgium. These three countries serve as an idea and the models for Malaysia in adapting the law on compulsory voting. Meanwhile, the recommendations that Malaysia should consider in changing the existing law relating to voting in Malaysia are presented and concluded in Chapter Four. Therefore, it is submitted that compulsory voting does give its very own potential to make citizens participate in the selection of government.